Black Brant Branta bernicla nigricans grit acquisition at Humboldt Bay, California, USA - Spragens, Kyle A.; Bjerre, Emily R.; Black, Jeffrey M. (Wildfowl, 2013)
The Black Brant Branta bernicla nigricans is a seagrass-obligate goose, strongly tied to the estuaries of the Pacific Flyway coast of North America. Black Brant are unique in that they remain reliant on their traditional food resource, in contrast to other Brent Goose populations that now readily switch to feed on agricultural land during migration and in winter. While Black Brant use of coastal estuaries within the Pacific Flyway is determined mainly by the presence of Common Eelgrass Zostera marina, accessible grit sites are a second, often overlooked, yet essential requirement that may be in part responsible for stop-over duration within these coastal estuaries. This paper synthesises existing literature and presents previously unpublished data from a series of studies conducted at Humboldt Bay, California, describing the role and importance of grit sites to Black Brant. We found that the local environment influences gizzard grit composition and, although evidence for grit selectivity by Brant makes it challenging, it is possible to link a Brant’s current gizzard contents to a previously used bay or grit site. The interval between successive sightings of ringed individuals identified at the primary grit site varied (mean ± s.d. = 8.6 ± 9.6 days, range = 4.5–10.1 days). We suggest that, during spring staging, individual geese must weigh trade-offs of time spent taking grit with time lost for other activities – including foraging.